Alexithymia, empathy, emotion identification and social inference in anorexia nervosa: A case-control study. (August 2016) - Gramaglia, Carla; Ressico, Francesca; Gambaro, Eleonora; Palazzolo, Anna; Mazzarino, Massimiliano; Bert, Fabrizio; Siliquini, Roberta; Zeppegno, Patrizia
Abstract: Alexithymia, difficulties in facial emotion recognition, poor socio-relational skills are typical of anorexia nervosa (AN). We assessed patients with AN and healthy controls (HCs) with mixed stimuli: questionnaires (Toronto Alexithymia Scale-TAS, Interpersonal Reactivity Index-IRI), photographs (Facial Emotion Identification Test-FEIT) and dynamic images (The Awareness of Social Inference Test-TASIT). TAS and IRI Personal Distress (PD) were higher in AN than HCs. Few or no differences emerged at the FEIT and TASIT, respectively. Larger effect sizes were found for the TAS results. Despite higher levels of alexithymia, patients with AN seem to properly acknowledge others' emotions while being inhibited in the expression of their own. Highlights: Patients with Anorexia Nervosa show alexithymia and emotional difficulties. Assessment was performed with questionnaires, photographs and dynamic images. Higher levels of alexithymia in patients with AN are supported. Few or no differences emerged in facial emotion recognition and social inference. Patients acknowledge others' emotions but are inhibited in the expression of their own.